SITUATIONAL ANALYSIS OF ASHAS WITH RESPECT TO COMPREHENSIVE CHILD SURVIVAL PROGRAMME: A STUDY FROM CHIRAIGAON BLOCK OF DISTRICT VARANASI - Mohapatra, Archisman; Gupta, Manoj Kumar; Shivalli, Siddharudha; Mohapatra, Sadhu Charan (Indian Journal of Community Health, 2011)
Research question: What proportions of the ASHAs are performing according to the training they have received under the Comprehensive Child Survival Programme (CCSP)? Objective: To analyze the ASHAs’ practice with respect to CCSP in related situations. Study design: Cross-sectional study. Study location: Chiraigaon Community Development Block, Varanasi Material and method: 173 out of the total 240 ASHAs (~72%) in the selected Chiraigaon Community Development Block of Varanasi were randomly selected and interviewed using a pre-designed and pre-tested questionnaire pertinent to CCSP. Only the first response was recorded. Results: All the ASHAs interviewed claimed that the CCSP training has helped them perform better in the community. Ninety-eight percent of the ASHAs knew that a new born weighing >2.5 kgs at birth is considered to be normal. Only ~ 63% (109) of the ASHAs were found to be home-visiting such newborns as per the CCSP recommendation. The percentage was found to be just 43% for the properly scheduled home visits of LBW newborns. The difference was found to be statistically significant (p<0.001). Almost 80% ASHAs estimated that their average home visit spans for at least 30 minutes. Just about a third of the interviewees suggested that a baby should be bathed only after the first 6 days while one-third said that they advise massaging for the newborn only after the first week. ASHAs rarely used a thermometer to assess the baby’s temperature. Around 56% were confident about using a thermometer. Nearly 90% participants claimed of explaining about Kangaroo Mother Care to the parturient and/or family. Majority of the ASHAs (92%) emphasized upon non-discontinuation of breast feeding for the baby during diarrhoeal episodes. However, only 44% revisited such babies. Conclusion: In most cases it is well evident that CCSP training has been taken up well by the ASHAs. The training may be refreshed.